Multilateral Environmental Agreements up to 2050: Are They Sustainable Enough? - Christoph Jeßberger (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
Today, reducing CO2 emissions is a global target which nearly all countries in the worldprioritize. Some countries have ratified up to 30 multilateral environmental agreementsregarding the atmosphere up to 2006. This number has been surging since 1989 after theratification of the Montreal Protocol. Following the findings of the inverted U-shapedEnvironmental Kuznets Curve and applying a spline model, I can show the beneficialimpact of the rising number of multilateral environmental agreements on the forecastsof CO2 emissions up to 2050. My results indicate that the number of atmosphere-relatedmultilateral environmental agreements generates good will among global cooperationefforts towards reducing CO2 emissions and therefore provides a good basis foreffective programs to stop climate change.
Keywords: C13; E17; F53; Q51; Q56; 330; Climate change; CO2 emissions; environmental agreements; forecasting; spline model; Klimaschutz; Umweltabkommen; Nachhaltige Entwicklung; Environmental Kuznets Curve; Welt